Pengaruh Kedisiplinan Belajar Terhadap Hasil Belajar Peserta Didik Kelas VIII di SMP Negeri 1 Amurang Timur - Mangantes, Meisie; Lempoy, Amelia Marshanda; Kasenda, Rinna Y. (Peneliti.net, 2023)
This research aims to determine the influence of learning discipline on the learning outcomes of Class VIII students at SMP Negeri 1 Amurang. This research is a quantitative approach, with correlational methods. The population members in this study were all class VIII students at SMP Negeri 1 East Amurang, totaling 200 students. The sample size was set at 15%, so there were 30 students who were members of the sample. The technique used in sampling is the Random Sampling technique. The data collection technique for variable X uses a questionnaire and data for variable Y uses documentation. The data analysis technique for hypothesis testing uses simple regression analysis, which is preceded by testing the requirements for parametric analysis, namely data normality and linearity tests. The results of the hypothesis testing analysis of this research show that there is an influence of learning discipline on student results, the regression equation Y = 8.11 + 0.89. The significance of the regression equation can be tested using the calculated F value. It turns out that the calculated F value is greater than the F table, so the Ha hypothesis is accepted. The conclusion is that there is an influence of learning discipline on student learning outcomes, this is shown by the regression coefficient (F) value of 95.08 with a significance of 0.000.